Utilizing a unique animal model to better understand human temperament. (April 2017) - Turner, Cortney A; Flagel, Shelly B; Blandino, Peter; Watson, Stanley J; Akil, Huda
Highlights: Temperament in humans can be studied as individual differences in animal models. The hippocampus integrates the brain's response to stress, fear and drugs of abuse. FGF2 plays a role in anxiety, depression, PTSD and addiction-related behaviors. Abstract : Individual differences in temperament are associated with psychopathology in humans. Moreover, the relationship between temperament and anxiety-, depression-, PTSD- and addiction-related behaviors can be modeled in animals. This review will highlight these relationships with a focus on individual differences in the response to stressors, fear conditioning and drugs of abuse using animals that differ in their response to a novel environment. We will discuss behavioral and neurobiological commonalities amongst these behaviors with a focus on the hippocampus and, in particular, growth factors as promising novel targets for therapeutic intervention.